Rotten - Northrop, Michael (Scholastic Press, 2013)
When troubled sixteen-year-old Jimmer "JD" Dobbs returns from a mysterious summer "upstate" he finds that his mother has adopted an abused Rottweiler that JD names Johnny Rotten, but soon his tenuous relationship with the dog is threatened.